(untitled) (Fountain Journal of Natural and Applied Sciences, 2018)
The Internet is a network of networks, which serves as a tool that provides the fastest and latest information on what goes on around the world. In Nigeria, a large number of Institutions are still lagging behind in the area of Internet provision and connectivity. This work focuses on the challenges and prospects of Internet connectivity in developing universities in Nigeria, taking Fountain University, Osogbo as a case study. Data were gathered from records and documents reviewed from the ICT Unit of the university. Assessment through logs, diaries and documentations with Internet network survey was carried out all over the campus. Technical and administrative challenges were found and some prospects were recommended. Keywords: Internet Challenges, Prospects, Nigerian Universities, Network Connectivity